2006
DOI: 10.1007/s10522-006-9029-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased resistance of lipofuscin-loaded prematurely senescent fibroblasts to starvation-induced programmed cell death

Abstract: Alterations of cellular structures often found in ageing cells is mainly the result of production of reactive oxygen species and a consequence of aerobic life. Both oxidative stress and decreased degradative capacity of lysosomal system cause accumulation of intralysosomal age-related pigment called lipofuscin. To investigate the influence of lipofuscin on cell function, we compared survival of lipofuscin-loaded and control human fibroblasts following complete starvation induced by exposure to phosphate-buffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…The current study is a continuation of the recently presented work of our group, showing that lipofuscinloaded cells are more resistant to cell death (Stroikin et al 2007). Here, instead of studying the apoptotic response, we focus on the effects of lipofuscin on Fig.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The current study is a continuation of the recently presented work of our group, showing that lipofuscinloaded cells are more resistant to cell death (Stroikin et al 2007). Here, instead of studying the apoptotic response, we focus on the effects of lipofuscin on Fig.…”
Section: Discussionsupporting
confidence: 63%
“…In opposition, some researchers doubt that a convincing evidence of deleterious effects of lipofuscin has ever been demonstrated . Moreover, we recently showed that moderate levels of lipofuscin have protective effects on cell survival during nutritional deprivation (Stroikin et al 2007). The previously suggested idea, that lipofuscin permanently occupies active sites of lysosomal enzymes, preventing their translocation to the cytosol and engagement in programmed cell death during lysosomal stress, is consistent with the present findings of decreased cytosolic translocation of cathepsin D in lipofuscin-loaded cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, however, a paper (Stroikin et al 2007) was published in Biogerontology that attributed to lipofuscin a new and stabilizing effect on lysosomes of starved fibroblasts. In that study it was concluded that lipofuscin in moderate amounts renders cells more, not less, resistant to starvation.…”
Section: Sirsmentioning
confidence: 99%